Viability of mycelial growth of Coprinus comatus in culture medium based on organic residues - Almeida, Laís Bentes de (2012)
The objective of this work was to evaluate the mycelial growth of the Coprinus comatus strain CCO 01/01 in culture based on organic residues of Saccharum officinarum (sugarcane bagasse), Citrus sinensis (orange bagasse), Ananas comosus (pineapple residues) and Musa sp. (banana leaf), supplemented with wheat bran in the proportions of 0, 10 and 20%, kept at 27°C. The mycelial growth of C. comatus was evaluated daily by measurement of the diameter of the colony during seven days of incubation. The banana leaf was considered the best residue for the cultivation of the C. comatus even without supplementation, meaning lower production costs. The supplementation of pineapple residues with 10% of wheat bran favored fungi growth. Sugar-cane bagasse was suitable for the growth of the C. comatus provided it is enriched with wheat bran. The orange bagasse, without pH correction, was not appropriate for the mycelial growth of C. comatus.